2018
DOI: 10.1507/endocrj.ej18-0187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of low androgen to gastroesophageal reflux symptoms

Abstract: The aim of this study was to determine the relationships between free testosterone (FT) level and parameters including laboratory data and data from questionnaires and to determine symptoms leading to the detection of late onset hypogonadism (LOH). We retrospectively reviewed medical records of patients in whom serum FT was measured in our hospital. Aging Male Symptoms (AMS) score, self-rating depression scale (SDS) and frequency scale for the symptoms of gastroesophageal reflux disease (FSSG) score were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Most LOH patients are over the age of 50 years and the average age when LOH develops is in the 60s [ 19 , 20 ]. The prevalence of LOH in our study was lower than that in a previous study conducted in a general population (48.7% in the present study vs. 58.0% in the general population [ 21 ]). However, the prevalence of LOH in individuals under 50 years of age was almost the same (46.7% vs. 44.6%) and the prevalence of LOH in individuals over 50 years of age was lower in the present study (55.6% vs. 67.2%).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Most LOH patients are over the age of 50 years and the average age when LOH develops is in the 60s [ 19 , 20 ]. The prevalence of LOH in our study was lower than that in a previous study conducted in a general population (48.7% in the present study vs. 58.0% in the general population [ 21 ]). However, the prevalence of LOH in individuals under 50 years of age was almost the same (46.7% vs. 44.6%) and the prevalence of LOH in individuals over 50 years of age was lower in the present study (55.6% vs. 67.2%).…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, the FSSG score, which has been reported to be inversely correlated with serum FT level [ 21 ], was not significantly increased in the LOH group (median, 11) compared to that in the non-LOH group (median, 8) in post COVID-19 condition. It has been reported that gastroesophageal reflux disease (GERD) and laryngopharyngeal reflux disease can be complications of COVID-19 [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the patients’ main disorders and past medical histories was obtained from hospital medical records. Information on age, gender, race, body mass index (BMI), and self-rating depression scale (SDS) was also obtained [ 12 ]. Information on the following biochemical parameters was also obtained: white blood cells, red blood cells, hemoglobin, hematocrit and platelets for blood cell counts; 25D, 1,25D, calcium (Ca), corrected Ca (cCa), inorganic phosphate (iP), cCa × iP, alkaline phosphatase (ALP), bone-specific alkaline phosphatase (BAP), and intact PTH for bone metabolism; total bilirubin, total protein, albumin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), γ-glutamyl transpeptidase (γGTP), sodium, potassium, chloride, magnesium, blood urea nitrogen (BUN), creatinine and estimated glomerular filtration rate (eGFR) for liver and renal functions; prothorombin time-international normalized ratio (PT-INR), activated partial thromboplastin time (APTT), and d-dimer for coagulatory markers; C-reactive protein (CRP), erythrocyte sedimentation rate in one hour (ESR), ferritin, 50% hemolytic unit of complement (CH50) and angiotensin-converting enzyme (ACE) for inflammatory markers; and hemoglobin A1c (HbA1c), plasma glucose, total cholesterol, uric acid, adrenocorticotropic hormone (ACTH), cortisol, prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), growth hormone (GH), thyroid-stimulating hormone (TSH), free thyroxine (FT4), ratio of TSH/FT4, and total testosterone for endocrine and metabolic markers.…”
Section: Methodsmentioning
confidence: 99%
“…During the physiological process of aging, four hormone systems demonstrate declines in circulating hormone concentrations, namely, dehydroepiandrosterone and its sulfate in "adrenopause", estrogen in "menopause", testosterone in "andropause", and the GH/IGF-1 axis in "somatopause" [2][3][4]. Among them, serum IGF-1 levels peak in the second decade of life, but subsequently decline rapidly until the sixth decade, when they plateau [5].…”
Section: Introductionmentioning
confidence: 99%